(untitled) - Linzer, Richard (Danvers, MA, 2007)
As many financial managers of nonprofit agencies and institutions will tell you, the bottom line, which reflects donations, reserves, and capital projects, contains a nasty little secret: much of it is unavailable for daily operations, and many nonprofit organizations are significantly strapped for cash. Consultants Linzer and Linzer go beyond the desperation bake sale to give managers skills in managing cash flow and using credit to ensure the doors of that successful capital project stay open and staffers can meet client needs on a long-term basis. They believe their ideas apply to both small and large agencies and institutions, making a case for managing cash flow through efficient monitoring and analysis, creating and maintaining a good relationship with your banker, dealing with both deficits and capital accumulation, and working with earned revenue and discounts.
Keywords: Cash flow,Nonprofit organizations,Chu kỳ tiền mặt; Finance